Late Neutrophil Priming Following a Single Session of High-intensity Interval Exercise - de Oliveira Ottone, Vinícius; Costa, Karine Beatriz; Tossige-Gomes, Rosalina; de Matos, Mariana Aguiar; Brito-Melo, Gustavo; Magalhaes, Flavio de Castro; Esteves, Elizabethe Adriana; Amorim, Fabiano; Rocha-Vieira, Etel (International Journal of Sports Medicine, 2019)
This study evaluated the effect of an acute high-intensity interval exercise (HIIE) session on the function of human neutrophils. Twelve sedentary men performed a HIIE session (8 bouts of 60 s at 90% of peak power, intercalated with 75 s of active recovery at 30 W). Neutrophils were collected before, 30 min and 24 h after the exercise session for the evaluation of phagocytic capacity, expression of phagocytic receptors, reactive oxygen species generation, and redox status. 24 h after the HIIE session, an increase was observed in both neutrophil phagocytic capacity and yeast-induced generation of reactive oxygen species, which indicates neutrophil priming in response to an acute HIIE session. Neutrophils also presented an increase in superoxide dismutase activity 24 h after the exercise. Improvement in neutrophil function was accompanied by increased serum levels of IL-8 and increased concentration of plasma lactate dehydrogenase. Our findings show a late activating effect of one HIIE session on neutrophils. We propose that priming of neutrophils by HIIE may play a role in skeletal muscle inflammation after exercise.
Keywords: phagocytosis; superoxide dismutase; reactive oxygen species; inflammation